2003
DOI: 10.1002/bjs.4426
|View full text |Cite
|
Sign up to set email alerts
|

Late complications after ligation and bypass for popliteal aneurysm

Abstract: Ligation and bypass does not always abolish blood flow in the sac of a popliteal aneurysm. It may be associated with continued expansion and late complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 7 publications
3
35
0
4
Order By: Relevance
“…Symptoms have been described in 8-17%. 13,15,28,29 However, we found that, following proximal and distal ligation and bypass, no popliteal aneurysm developed either symptoms or ultrasound-detected flow.…”
Section: Fate Of the Excluded Aneurysmmentioning
confidence: 63%
See 2 more Smart Citations
“…Symptoms have been described in 8-17%. 13,15,28,29 However, we found that, following proximal and distal ligation and bypass, no popliteal aneurysm developed either symptoms or ultrasound-detected flow.…”
Section: Fate Of the Excluded Aneurysmmentioning
confidence: 63%
“…[12][13][14][15][16][17][18] This is usually due to thrombosis but thrombus from the aneurysm can embolise distally. About a quarter of popliteal aneurysms are associated with intermittent claudication, either from thrombosis, repeated micro-emboli or combined stenotic arterial disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…U svojoj studiji Tielliu i sur. navode da je u 57 sluča-jeva poplitealnih aneurizmi podvrgnutih endovaskularnom liječenju dvogodišnja prohodnost iznosila 77 %, što se podudara s drugim recentnim studijama 1, 21 . U svome istraživanju Lovegrove i sur.…”
Section: Dominacija Medijalnog Pristupaunclassified
“…U ovoj metodi ne postoji mogućnost korištenja prirodnih transplantata, već isključivo umjetnih materijala, kako bi se uspostavio normalan krvotok što je lošija varijanta, jer oni brže podliježu trombozi i začepljenju. Također, kod nekih pacijenata dolazi do prodora krvi u aneurizmu s distalne strane te njezinog daljnjeg rasta, embolizacije tromba i pojave distalne ishemije uda 1, 21 . U nekih slučajeva zamijećena je i migracija stenta, odnosno njegovo pomicanje te gubitak funkcije, iako je prvotno bio ispravno stavljen i pozicioniran.…”
Section: Zaključakunclassified